Implementation of a Talent Management Program to Support the Economic Independence of the Visually Impaired Disabilities at Urunan Kebaikan Foundation - Reginald, Azel Raoul; Supardi, Supardi; Sriyono, Sriyono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The increasing number of visually impaired individuals facing economic challenges has prompted various organizations to seek effective solutions. This study explores the implementation of a talent management program at the Urunan Kebaikan Foundation to support the economic independence of visually impaired individuals. The problem formulation addresses the challenges faced by visually impaired individuals in achieving economic self-sufficiency and how a structured talent management program can mitigate these challenges. The research aims to assess the effectiveness of this program in enhancing the economic capabilities of the participants. A qualitative method with a case study approach was used to gather in-depth data from program participants, administrators, and related stakeholders. The research findings indicate that the talent management program has significantly improved the economic skills and opportunities for visually impaired individuals, leading to increased independence and better quality of life. The study concludes that a well-implemented talent management program can be a pivotal factor in empowering visually impaired individuals economically.